The Challenges of Democracy in the Era of Globalization for the Purpose of Preventing Money Politics in Elections - Saputri, Wahyuningtyas Dwi; Prayogo, Bagus Edi (Law Research Review Quarterly, 2018)
Globalization according to the big Indonesian dictionary is the process of entry into the scope of the world. In this case it means that the world is without limits. Easily enter and exit information. This has resulted in various positive and negative impacts. The positive impact of the existence of globalization adds insight into knowledge about what is happening in the outside world and adds enthusiasm in making various useful innovations along with the passage of human life. And the negative impact of globalization itself is the higher level of fulfillment of human needs. From the influence of globalization can change the structure and structure to habits in society if not filtered properly. The effect of the high level of fulfillment of human needs causes many people to do various things in order to achieve these needs. One example that often occurs in the democratic life of the Indonesian people is money politics. Money politics is implemented by a handful of people who have personal goals and interests. This is certainly a violation in terms of democracy because it violates the principles in elections that have the principle of confidentiality, honesty, and fairness. The democratic party should be characterized by sportsmanship and honesty without coercion in choosing regional representatives. Ironically, money politics has always been a powerful way to win one of the regional representatives. People who are victims need to be educated so that there is no money politics in the election party.